Vignettes as tool for research and teaching in life course studies: Interdisciplinary approaches. (June 2017) - Kelly-Irving, Michelle; Soulier, Alexandra; Mabile, Laurence; Bartley, Melanie; Raynaud, Jean-Philippe; Panico, Lidia; Blane, David
Highlights: The life course framework provides an ideal setting for interdisciplinary research and teaching. We have developed a method to encourage researchers or students to get to grips with life course theories, principles and hypotheses. The method, its strengths and weaknesses are presented and discussed in this paper based on experience in both research and teaching settings. Abstract: Background: Interdisciplinary research and teaching often present similar challenges to investigators and teachers in higher education settings. Capturing and harnessing disciplinary knowledge from different fields to strengthen the process is desirable. However, in practice, this may be difficult to achieve. In this paper we set out a methodology developed in both research and teaching settings which has successfully brought researchers and participants from different disciplinary backgrounds together to work within a life course framework. Methods: The methodology centres on using what we will describe as vignettes, or descriptive case histories and is divided into three stages. In stage 1 participants work together to write a vignette based on instructions. In stage two, participants work together in a group to analyse and deconstruct a different vignette. Here In stage 3 all groups present and discussed the analysed vignettes. Results: We provide results from stage 1 on a specific vignette written by a group of participants. Here the participants get to grips with general life course concepts. In stage 2 participants learn about life course principles and constructs by deconstructing and analyzing a vignette. In stage 3 the participants are encouraged to shift from thinking about individuals, to population dynamics. Discussion: We discuss the strengths and limitations of this method within the context of interdisciplinary life course research and teaching in higher education. Conclusion: Using vignettes to both construct and deconstruct life courses has proved a useful tool for deriving new research questions and research material within the framework of life course theory.